2018
DOI: 10.1002/cb.1732
|View full text |Cite
|
Sign up to set email alerts
|

Implicit communication of food product healthfulness through package design: A content analysis

Abstract: How do food companies use package design to communicate healthfulness? The present study addresses this question by investigating the most typical implicit package design elements used by food companies for their health‐positioned food products. Using a content analysis on the packaging design of 12 food product categories across two countries (Denmark and the United States), our findings indicate that (a) implicit package design elements (colors, imagery, material, and shape) differ between health‐positioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 65 publications
0
37
0
Order By: Relevance
“…Packaging is integral to the “Four Ps” in the “marketing mix” concept and is a promotional tool for products and brands alike . Packaging consist of both structural (eg, packaging material, shape, size, weight, and texture, and graphic features) and verbal design features that are placed on the product (such as textal information) . Silayoi et al stated that “packaging represents the salesman on the shelf.” In addition, Clement describes product packaging as a means of attracting consumers' attention to the brand or the product.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Packaging is integral to the “Four Ps” in the “marketing mix” concept and is a promotional tool for products and brands alike . Packaging consist of both structural (eg, packaging material, shape, size, weight, and texture, and graphic features) and verbal design features that are placed on the product (such as textal information) . Silayoi et al stated that “packaging represents the salesman on the shelf.” In addition, Clement describes product packaging as a means of attracting consumers' attention to the brand or the product.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Adam et al and Freire el al found that nutritional information displayed on packaging has a very important role here. This is because consumers have become more health conscious and are now gravitating toward the nutritional values displayed on the product package, especially in terms of natural and organic products. In their study, they found that the implicit message communicated by structural packaging elements differs between health‐positioned and regular products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These two results reveal information that supports how the children were able to determine their choice of which toys were most liked. The material was a design dimension that caught their attention (Kwon et al, 2002;Lin, 2010;Festila and Chrysochou, 2018) and how boys need to visit more times than girls to do a decision-making. The results obtained using the traditional methods of icons and toys assessment were enhanced with the use of the data extracted from eye movement.…”
Section: Discussionmentioning
confidence: 99%
“…These three attributes give a complete "object representation" leading to more complex cognitive processes, giving us the ability to understand the visual elements. Through form, texture, objects, color, and intensities, a familiar stimulus to children could stand out and serve as an attraction to attractor the consumer's attention (Kwon et al, 2002;Luo, 2006;Lin, 2010;Festila and Chrysochou, 2018). Specifically, color plays a fundamental role as a factor of aesthetic attractiveness to everybody, from a perceptual aspect (Helo et al, 2014) to the emotional aspect (Green-Armytage, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Only unprocessed hen egg products were taken for further analysis. Images of the egg boxes were saved and subjected to content analysis, similar to previously applied to organic and health-food packaging [20,21]. All 50 eggboxes examined displayed at least one explicit written message, such as "a good source or omega-3", "from free-range hens", or "great taste" (Table 1).…”
Section: Methodsmentioning
confidence: 99%